Quantitative HBsAg (qHBsAg) as an end point to stop nucleos (t) ide analogues in chronic hepatitis B: a meta-analysis with meta-regression - Lim, Seng Gee (Elsevier BV, 2022)
10.1016/s0168-8278(22)02033-5